Manganese-Doped N-Hydroxyphthalimide-Derived Carbon Dots-Theranostics Applications in Experimental Breast Cancer Models - Adrian Tiron; Corneliu S. Stan; Gabriel Luta; Cristina M. Uritu; Irina-Cezara Va; Gabriela D. Stanciu; Adina Coroaba; Crina E. Tiron (MDPI AG, 2021)
Background: Theranostics, a novel concept in medicine, is based on the use of an agent for simultaneous diagnosis and treatment. Nanomaterials provide promising novel approaches to theranostics. Carbon Dots have been shown to exhibit anti-tumoral properties in various cancer models. The aim of the present study is to develop gadolinium, Fe3+, and Mn2+-doped N-hydroxyphthalimide-derived Carbon Dots. The resulted doped Carbon Dots should preserve the anti-tumoral properties while gaining magnetic resonance imaging properties. Methods: Normal and cancer cell lines have been treated with doped Carbon Dots, and the cell viability has been measured. The doped Carbon Dots that exhibited the most prominent anti-tumoral effect accompanied by the lowest toxicity have been further in vivo tested. Magnetic resonance imaging evaluates both in vitro and in vivo the possibility of using doped Carbon Dots as a contrast agent. Results: According to the results obtained from both the in vitro and in vivo experimental models used in our study, Mn2+-doped Carbon Dots (Mn-CDs-NHF) exhibit anti-tumoral properties, do not significantly impair the cell viability of normal cells, and reduce lung metastasis and the volume of mammary primary tumors while allowing magnetic resonance imaging. Conclusions: Our findings prove that Mn-CDs-NHF can be used as theranostics agents in pre-clinical models.